The impact of artificial intelligence on the labour market: risks and opportunities - Kryvonos, Ivan (Запоріжжя: НБ ТДАТУ, 2025)
The development of artificial intelligence is having a significant impact on the modern labour market, transforming both individual industries and the economy as a whole. Over the past decades, AI technologies, including machine learning, robotics and process automation, have penetrated all areas of life, from manufacturing and finance to medicine and education. This creates new business opportunities, increases production efficiency, improves the quality of services and reduces costs. However, along with its benefits, the introduction of AI also brings a number of challenges, especially in the context of the labour market. Thus, researching the impact of AI on the labour market is relevant and necessary to understand how technologies are changing the nature of work, what opportunities and risks they bring, and what measures are needed to minimise the negative consequences and maximise the positive effects of AI. This will allow developing strategies to adapt the labour market to new conditions, ensure fair redistribution of benefits and maintain socio-economic stability.
Keywords: artificial intelligence; finance to medicine; risks; opportunities